Impact of regulatory changes on economic feasibility of distributed generation solar units - Gabriel Nasser Doile de Doyle; Paulo Rotella Junior; Luiz Célio Souza Rocha; Priscila França Gonzaga Carneiro; Rogério Santana Peruchi; Karel Janda; Giancarlo Aquila (Charles University in Prague, Institute of Economic Studies (IES), 2022)
The Brazilian National Electrical Agency (ANEEL) proposed in 2019 that the costs for accessing the electricity grid should be shared among all consumers. This would do away with cross-subsidies where normal consumers without installed solar distributed generation (DG) units effectively cover the costs of access to the grid for consumers with DG units. We compared the viability of two scenarios, one before and the other after the proposed changes, to understand how this legislature will affect the viability of DG projects in Brazil. We did this by studying all 5 regions covering the whole Brazilian area by analyzing data on average solar radiation, demand, and energy prices. We conducted stochastic analysis by varying the investment costs, demand, and energy prices, for DG solar plants. Lastly, we conducted scholastic analysis for the national scenario by varying the Discount Rate (DR). We confirmed that there is a statically significant reduction in economic viability for DG solar units in Brazil if the proposed legislation were to be enacted, while the payback period and other financial indicators differ across regions. We confirmed that solar radiation is not the only decisive factor in determination of economic viability of DG solar production.
Keywords: Q41; Q48; 330; Distributed Generation; Regulation Policy; Cross-subsidies; Micro-Power Plants; Economic Feasibility Analysis; Solar Photovoltaic Energy